Altered Expression of Hematopoiesis Regulatory Molecules in Lipopolysaccharide-Induced Bone Marrow Mesenchymal Stem Cells of Patients with Aplastic Anemia - Chandra Prakash Chaturvedi; Naresh Kumar Tripathy; Ekta Minocha; Akhilesh Sharma; Khaliqur Rahman; Soniya Nityanand (Stem Cells International)
We have investigated the expression of RNA transcripts of hematopoiesis regulatory molecules, viz., macrophage inflammatory protein (MIP)-1α, tumor necrosis factor (TNF)-α, granulocyte colony-stimulating factor (G-CSF), stromal cell-derived factor (SDF)-1α, stem cell factor (SCF), and transforming growth factor (TGF)-β in lipopolysaccharide-induced bone marrow mesenchymal stem cells (BM-MSCs) and levels of their soluble forms in the culture supernatants of BM-MSCs and BM plasma of patients with acquired aplastic anemia (AA) (n=29) and controls (n=29). The BM-MSCs of AA patients as compared to controls had markedly lower expression of MIP-1α transcripts (p<0.001), higher expression of TNF-α (p<0.001), G-CSF (p<0.001), and SDF-1α (p<0.01) transcripts, and no difference in the expression of SCF and TGF-β transcripts. The culture supernatants of BM-MSCs and BM plasma of AA patients in comparison to controls also had lower levels of MIP-1α (p<0.01 and p<0.001, respectively) and higher levels of TNF-α (p<0.05 for both) and G-CSF (p<0.05 and p<0.001, respectively) but with no difference in the levels of SDF-1α and SCF. The levels of TGF-β were although similar in culture supernatants of BM-MSCs of both the groups, but they were significantly lower in BM plasma of the patients than controls (p<0.001). Our data shows that BM-MSCs of AA patients have altered expression of hematopoiesis regulatory molecules suggesting that they may have a role in the pathogenesis of the disease.